Assessment of collective immunity to enteric hepatitis viruses in the Kyrgyz population - A. Yu. Popova; A. Yu. Gorbunova; Yu. V. Ostankova; S. A. Egorova; B. K. Arykbaeva; Z. O. Abdrakhmanova; U. S. Karataeva; D. E. Reingardt; A. R. Ivanova; A. N. Shchemelev; I. V. Drozd; O. B. Zhimbaeva; et al. (Инфекция и иммунитет)
The problem of viral hepatitis A (HA) and E (HE), has remained relevant for many decades. According to estimates by the World Health Organization, millions of people are exposed annually to the risk of infection with these hepatitis A (HAV) and E (HEV) viruses. Because HA and HE can be asymptomatic, their true prevalence is very difficult to estimate. The aim was to assess seroprevalence of HAV and HEV infections in the Kyrgyz Republic, taking into account the infectious and vaccination status and socio-demographic characteristics of volunteers.